The Influence of Profitability and Company Size on Tax Avoidance (A Case Study of Mining Companies Listed on the Indonesia Stock Exchange in 2018-2022) - Ridha Azka Raga; Wuwuh Andayani; Husna Putri Pertiwi; Julaeha; Dwikora Harjo (Yayasan Ilomata, 2023)
Tax avoidance is a deliberate strategic approach that companies employ to reduce their tax liabilities while remaining compliant with relevant tax regulations. The complexity of tax avoidance arises from its dual nature, where, on one side, it remains within the bounds of legality, and yet, on the other side, it is deemed undesirable by the government due to its adverse impact on national revenue. The objective of this research is to investigate how both the size and profitability of a company influence its engagement in tax avoidance between mining companies listed on the Indonesia Stock Exchange (BEI) from 2018 to 2022. This research utilized a descriptive quantitative methodology and for sample was selected through purposive sampling, identifying 14 companies meeting predefined criteria. The data collected was subjected to analysis using IBM SPSS Statistics 25, which included Classical Assumption Tests, Multiple Linear Regression Analysis, and Hypothesis Testing. The results of this study indicated a noteworthy impact of profitability on tax avoidance, while the size of the company did not demonstrate a significant influence on tax avoidance. Moreover, the observation revealed that the joint consideration of both profitability and company size had a significant impact on tax avoidance.